2016
DOI: 10.1007/s12028-016-0363-6
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors for Early Seizure in Patients with Traumatic Brain Injury: Analysis from National Trauma Data Bank

Abstract: In-hospital seizures occur in 0.4% of all TBI patients. Although infrequent, seizure occurrence is associated with higher rates of hospital complications such as pneumonia and ARDS and is an independent predictor of longer hospital stay and worse hospital outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
51
1
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(65 citation statements)
references
References 26 publications
9
51
1
4
Order By: Relevance
“…5 Several studies have identified risk factors for occurrence of acute symptomatic seizure (ASz), such as older age, alcoholism, art of trauma, depressed skull fracture, dura penetration, penetration injuries and cortical injuries. [6][7][8][9][10][11][12] Previously, we were able to show a strong correlation between occurrence of seizures and aSDH, which was well in line with previous studies, whereas opinions regarding seizures and cSDH are contradictory. [6][7][8][9][10][11][12] Previously, we were able to show a strong correlation between occurrence of seizures and aSDH, which was well in line with previous studies, whereas opinions regarding seizures and cSDH are contradictory.…”
Section: Introductionsupporting
confidence: 91%
See 1 more Smart Citation
“…5 Several studies have identified risk factors for occurrence of acute symptomatic seizure (ASz), such as older age, alcoholism, art of trauma, depressed skull fracture, dura penetration, penetration injuries and cortical injuries. [6][7][8][9][10][11][12] Previously, we were able to show a strong correlation between occurrence of seizures and aSDH, which was well in line with previous studies, whereas opinions regarding seizures and cSDH are contradictory. [6][7][8][9][10][11][12] Previously, we were able to show a strong correlation between occurrence of seizures and aSDH, which was well in line with previous studies, whereas opinions regarding seizures and cSDH are contradictory.…”
Section: Introductionsupporting
confidence: 91%
“…In particular, acute (aSDH) and chronic subdural hematoma (cSDH) have been shown to be one of the major predictors for ASz and a high cumulative probability of 27.8% for late seizures occurring within 2 years. [6][7][8][9][10][11][12] Previously, we were able to show a strong correlation between occurrence of seizures and aSDH, which was well in line with previous studies, whereas opinions regarding seizures and cSDH are contradictory. 11,13,14 The reported incidence of seizures in cSDH varies in between 2% and 42%, and some predictors, such as alcoholism, male sex, low Glasgow Coma Scale (GCS) at admission, previous stroke, and hematoma density, were identified in a smaller number of patients.…”
Section: Introductionsupporting
confidence: 91%
“…Большинство опубликованных ранее исследований, посвященных ПТП и эпилепсии, проводились на постгоспитальном этапе или с анализом ретроспективных данных [15,17,19,27,28]. В настоящей работе был осуществлен проспективный анализ ПТП, возникших в острый период ЧМТ и в течение 2 следующих лет.…”
Section: Discussionunclassified
“…По данным литературы [13][14][15][16][17][18][19][20][21][22][23], заболеваемость ранними и поздними ПТП составляет от 2 до 19% и при определенных условиях может достигать 30% и более. Доля пациентов с ранними (18,1%) и поздними (6,3%) приступами у обследуемых пациентов в настоящем исследовании находилась в пределах указанных диапазонов.…”
Section: Discussionunclassified
See 1 more Smart Citation